EUROPEAN UNIFICATION AND EUROPEAN INTEGRATION AS A PHILOSOPHICAL PRINCIPLE - GHIDIRMIC, Bogdan; MATEI, Alexandru (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
In the mentioned coordinates of the European studies, the European unification is an attempt to establish a conceptual, philosophical framework for these studies, oriented, according to their stage, towards the fundamental aspects: the specificity of Europe and the European crisis; European unification; the cardinal philosophical problems of European unification and the resistance it faces. Using disciplinary approaches (economics, political science, sociology, history, etc.), she seeks to clear the philosophical side and support it, away from the positivist rendering of what is, but also from the usual slip in generalizations without sufficient basis, which is encouraged by generous topics, which are in public controversy.